2020
DOI: 10.31234/osf.io/k95rj
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Gratitude Reduces Consumption of Depleting Resources

Abstract: Sustaining finite public resources presents a dilemma between acting in self-interest for present benefit versus working toward long-term collective gain. Given gratitude’s links to prosociality and self-control, the present studies investigated whether gratitude would promote sustainable resource extraction under conditions of rapidly depleting resources. In Study 1 (N=155), participants were randomly assigned to experience an emotional state (gratitude or neutral) prior to playing a resource dilemma game whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Gratitude induced via a recollection task (but not general positive affect) caused participants to extract fewer excess resources (points) in a commons dilemma task, which although not framed as environmental per se, mirrors natural resource dilemmas (e.g., fishing, carbon emissions, etc.) [43]. A recent dissertation by Hamilton [44] found that spiritual gratitude rituals towards nature were associated with environmental values, but there was no association between gratitude rituals and pro-environmental behaviors.…”
Section: Emotions and Pro-environmental Behaviormentioning
confidence: 99%
“…Gratitude induced via a recollection task (but not general positive affect) caused participants to extract fewer excess resources (points) in a commons dilemma task, which although not framed as environmental per se, mirrors natural resource dilemmas (e.g., fishing, carbon emissions, etc.) [43]. A recent dissertation by Hamilton [44] found that spiritual gratitude rituals towards nature were associated with environmental values, but there was no association between gratitude rituals and pro-environmental behaviors.…”
Section: Emotions and Pro-environmental Behaviormentioning
confidence: 99%
“…For example, it has been consistently demonstrated that help/gift recipients react prosocially toward the Helper, third-party individuals, the environment, and the future self (Beeler-Duden & Vaish, 2020;Dickens & DeSteno, 2016;Kates & DeSteno, 2020;McCullough et al, 2001). Gratitude also motivates the grateful person to care more about the wellbeing of the Helper and strengthen the relationship to the Helper (Algoe, 2012;Bartlett et al, 2012;Lambert et al, 2010).…”
Section: Introductionmentioning
confidence: 99%